Marcas da oralidade da escrita dos alunos do 9º ano do ensino fundamental (Escola Professor Paulo Freire - Presidente Médici/RO) - Souza, João Bosco de (2024)
This research discusses the importance of orality and writing in communication human, highlighting the primacy of speech as a fundamental form of interaction; is based on studies by Marcushi (2010), Koch (2013), Ilari (2009), Bagno (2007), among others that were used in order to delve deeper into the segments compounds for carrying out this research. Based on these reflections, the study has The objective is to carry out an analysis and observe the marks of orality in writing, in productions carried out by students, highlighting the sociolinguistic content present in each text. To make the research viable, we delimited the textual productions carried out by 9th year students at Escola Professor Paulo Freire, located in President Médici - RO. To achieve the results of this research, it was carried out, initially, a bibliographical survey, in order to support the construction of this research, after, samples were collected from 9th year students - final years, then carrying out exploratory field research. In addition Furthermore, the research also addresses historical aspects of English language teaching. Portuguese in Brazil, in addition to considerations on educational legislation. Finally, throughout this research it was observed that orality is seen as a form of self-transformation that requires a process of self-reflection and self-knowledge; It is It is important to highlight that, when seeking freedom, the individual must be aware of the forms of power that operate in your life and the practices that subject you to certain norms and values.